Crime and Violence in Development : A Literature Review of Latin America and the Caribbean - Heinemann, Alessandra (World Bank, Washington, DC, 2012)
The authors review the recent literature on crime and violence in Latin America and the Caribbean and present a broad overview of the main ideas and empirical findings. They provide estimates of the magnitude of the problem, trends, and the manifestations of crime and violence in Latin America. They also discuss the ways in which violence affects development, the root causes of violence, and the empirical evidence on the determinants of crime. The authors conclude by stressing that preventive measures and innovative social policies are efficient and underutilized strategies to address the problem and call for both more research and operational experimentation.